A Reflection on the Nexus between South African Land Reform Struggles and the Unresolved National Question. Issue 1 (2nd January 2023) - Xaba, Mzingaye Brilliant; Akinola, Adeoye O.
Abstract: The post-apartheid South African government continues to struggle with its transformation posture, including the quest to redress the racially based land inequalities that have plagued the country since its colonial past. The Covid-19 pandemic, the 2015 #RhodesMustFall and #FeesMustFall movements, and the July 2021 #FreeZuma violence have highlighted both the fragility and the resilience of South African political institutions. Since the formation of the Economic Freedom Fighters (EFF), a left-leaning and militant political party, in 2013, the South African land question has become more vociferously contested within government purview and in the public domain. Unresolved land issues have exposed the failure of the state to resolve one of its most sensitive national questions. We interrogate the land conflict and locate it within the broader national questions that have continued to haunt post-apartheid South Africa. Indeed, the South African land question must be understood holistically, and not solely as an agrarian question. Although the ANC-led government has implemented a land reform scheme under four pillars—land restitution, land redistribution, tenure security, and land development—there are still compelling cases of land hunger and conflict, as well as widespread confusion about the proposed land expropriation without compensation. Despite the rhetoric by government officials, we hold that the land debacle is a manifestation of a failing national question, state fragility, and an incomplete decolonisation process wherein the so-called "political power" held by the majority has not transformed into economic power and the effective redistribution of land to meet the targets of successive administrations.